The Influence of Mn2+ on DNA structure in the presence of Na+ ions: A Raman spectroscopic study. Issue 5 (2006) - Muntean Muntean, Cristina M. Cristina M.; Misselwitz Misselwitz, Rolf Rolf; Welfle Welfle, Heinz Heinz
Abstract : The influence of Mn 2+ ions on the structure of natural calf thymus DNA was studied by Raman spectroscopy. Measurements were done at room temperature and pH 6.2±0.2, in the presence of the physiological concentration of 150 mM Na + ions, and in the presence of Mn 2+ concentrations that varied between 0 and 600 mM. No condensation of DNA was observed at any of the Mn 2+ concentrations. At 5 mM Mn 2+ and 150 mM Na + no significant influence of Mn 2+ ions on the DNA structure can be observed. Compared with our previous results obtained at 10 mM Na + ions, binding of Mn 2+ ions to charged phosphate groups and to DNA bases is inhibited in the presence of 150 mM Na + ions. DNA backbone conformational changes were not observed in the whole concentration range of Mn 2+ ions as judging from the Raman spectra. No evidence for DNA melting was identified. A high Mn 2+ affinity for binding to guanine N7 and possibly, in a much lesser extent, to adenine have been found.